2003
DOI: 10.1137/s0036142901391451
|View full text |Cite
|
Sign up to set email alerts
|

On Optimal Finite-Difference Approximation of PML

Abstract: Abstract.A technique derived from two related methods suggested earlier by some of the authors for optimization of finite-difference grids and absorbing boundary conditions is applied to discretization of perfectly matched layer (PML) absorbing boundary conditions for wave equations in Cartesian coordinates. We formulate simple sufficient conditions for optimality and implement them. It is found that the minimal error can be achieved using pure imaginary coordinate stretching. As such, the PML discretization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 24 publications
2
68
0
Order By: Relevance
“…The discretization error is eliminated with the help of midpoint integration. This observation, as well as other related observations made in an earlier paper [24], unifies the seemingly unrelated ideas underlying material-based PMLs and differential equation-based local ABCs. We have exploited this link to obtain efficient corner absorbing elements, and have extended the idea to oblique corners, thus making the CFABCs applicable to convex polygonal domains.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The discretization error is eliminated with the help of midpoint integration. This observation, as well as other related observations made in an earlier paper [24], unifies the seemingly unrelated ideas underlying material-based PMLs and differential equation-based local ABCs. We have exploited this link to obtain efficient corner absorbing elements, and have extended the idea to oblique corners, thus making the CFABCs applicable to convex polygonal domains.…”
Section: Discussionsupporting
confidence: 86%
“…The (imaginary-layer) CFABCs, implemented in this paper, can be considered as the limiting case of PMDLs, where the real parts of the element lengths are zero. Based on Proposition 3.1 in Reference [24], which states that purely imaginary stretching is optimal for absorbing propagating waves, and also based on the numerical experiments presented in Reference [27], we note that the imaginary-layer CFABCs would be more accurate than the complex-layer CFABCs. Since complex-layer CFABCs are perfectly matched at the discrete level, they are expected to perform better than the discretized PMLs with exact integration.…”
Section: Relationship To Perfectly Matched Layers (Pmls)mentioning
confidence: 74%
See 2 more Smart Citations
“…The most robust application of this approach is the method of Perfectly Matched Layers (PML), introduced by Berenger (1994) and later interpreted and enhanced by several other researchers. Despite the conceptual difference between the material-based and local ABCs, Asvadurov et al (2003) showed that there is a mathematical link between the two, which is further simplified by Guddati and Lim (2004) who illustrated the superior performance of local ABCs over conventional PML.…”
Section: Introductionmentioning
confidence: 99%